NEEDS ANALYSIS AND DIGITAL FORMAT DEVELOPMENT OF INTERMEDIATE JAPANESE GRAMMAR LEARNING MATERIALS BASED ON JF STANDARD - Andi Irma Sarjani; Ifan Iskandar, Siti Gomo Attas (Adisam Publisher, 2024)
The purpose of this study is to investigate the extent to which Japanese language education standards, namely the JF Standard, are included in the existing Japanese grammar teaching materials. This study also examines the extent to which active learning is included in Japanese grammar teaching materials, and the extent to which the digital format of Japanese grammar teaching materials is adopted in existing teaching materials. This study uses research and development methods. The results showed that the Japanese education standard,namely the JF Standard, did not yet exist in the current Japanese grammar teaching materials,nor did the existing teaching materials adopt active learning and the format used was still anold format that did not use digital formats.